Application of compound viscosity reducer for low temperature transportation in Huabei oilfield. (February 2019) - Gao, X L; Wang, C F; Feng, J Z; Sun, Q; Xue, L Q; Ma, W N; Wang, H; Su, N; Liu, G Y; Liu, L F; Yue, L B
Abstract: Reducing the viscosity of heavy oil is one of the main works in oilfield development. This article chose the nonionic surfactant and anionic surfactant as the main agent, and after optimizing the proportion of combination and joining the functional additive, the compound viscosity reducer with dual function of viscosity reduction and pour point depression for low temperature transportation in pipelines is prepared. The compound viscosity reducer is non-toxic, safe and environmentally. Experiments show that when the concentration of the compound viscosity reducer is 0.05%, the freezing point of crude oil fall by more than 8 °C, and the viscosity reduction rate is more than 75%. After field application in Huabei oilfield, the average pipeline pressure drop is 0.6-1.5 MPa( the average pressure drop rate is 53%), which plays the important role for low temperature transportation in pipelines